Clinical utility of cerebrospinal fluid-derived circular RNAs in lung adenocarcinoma patients with brain metastases - Wang, Zhen; Yu, Ruoying; Chen, Xiaoxi; Bao, Hua; Cao, Ran; Li, An-Na; Ou, Qiuxiang; Tu, Hai-Yan; Zhou, Qing; Wu, Xue; Lin, Zhi-Bo; Wu, Yi-Long (Journal of translational medicine, 2022)
Background Free circular RNAs(circRNAs) escaping from primary lesion of cancer to brain are strictly regulated by blood–brain barrier and therefore cerebrospinal fluid (CSF) circRNAs have potential advantage in exploring biomarkers and mechanism of brain metastasis in lung cancer. Methods We collected paired cerebrospinal fluid, plasma and tumor tissues from 21 lung adenocarcinoma (ADC) patients with brain metastases (BM) and performed RNA sequencing. Results Compared to tumor tissue and plasma, circRNAs in CSF were characterized by lower number of spieces but higher abundance. Notably, CSF-circRNAs displayed high heterogeneity among different BM lung ADC patients. A total of 60 CSF-circRNAs was identified and associated with shorten overall survival. The circRNA-miRNA-mRNA network analysis revealed that the 60 CSF-circRNAs involved in cancer-associated pathways, and five of them showed strong association with WNT signaling pathway. Validation by RT-PCR of CSF and in vitro experiments of the five candidate circRNAs support their potential roles in cell proliferation and invasion. Conclusions In summary, our results depicted the heterogenous CSF-circRNAs profiles among BM lung ADC and implied that CSF-circRNAs may be promising prognosis-related biomarkers.